Tetrabutylammonium Iodide‐Catalyzed Radical Alkoxycarbonylation of 2‐Isocyanobiphenyls with Carbazates: Synthesis of Phenanthridine‐6‐carboxylates. Issue 9 (30th April 2014) - Li, Xiaoqing; Fang, Mingwu; Hu, Peizhu; Hong, Guo; Tang, Yucai; Xu, Xiangsheng
Abstract A practical and environmentally friendly strategy for generating alkoxycarbonyl radicals from readily available carbazates under metal‐free conditions has been developed. In the presence of tetrabutylammonium iodide and tert‐butyl hydroperoxide, 2‐isocyanobiphenyls smoothly underwent radical alkoxycarbonylation with carbazates to afford phenanthridine‐6‐carboxylates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>